2023
DOI: 10.1530/ec-23-0043
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous cortisol secretion in patients with primary aldosteronism: prevalence and implications on cardiometabolic profile and on surgical outcomes

Abstract: Purpose: To evaluate the prevalence of autonomous cortisol secretion (ACS) in patients with primary aldosteronism (PA) and its implications on cardiometabolic and surgical outcomes. Methods: A retrospective multicenter study of PA patients who underwent 1mg-dexamethasone suppression test (DST) during diagnostic work-up in 21 Spanish tertiary hospitals. ACS was defined as a cortisol post-DST >1.8µg/dL (confirmed ACS if >5µg/dL and possible ACS if 1.8-5µg/dL) in absence of specific clinical features of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, the coexistence of aldosterone and cortisol hypersecretion has been reported in about 30% of patients with primary aldosteronism ("Connshing syndrome") [31,32]. Patients with cosecretion of aldosterone and cortisol have a higher prevalence of hypertension (odds ratio [OR] 7.7, 95% CI 2.64-22.32) than patients with MACS without primary aldosteronism.…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition, the coexistence of aldosterone and cortisol hypersecretion has been reported in about 30% of patients with primary aldosteronism ("Connshing syndrome") [31,32]. Patients with cosecretion of aldosterone and cortisol have a higher prevalence of hypertension (odds ratio [OR] 7.7, 95% CI 2.64-22.32) than patients with MACS without primary aldosteronism.…”
Section: Pathogenesismentioning
confidence: 99%
“…35 In APA patients, cosecretion of cortisol evidenced by the 1 -mg dexamethasone suppression test is common (eg, one -third of patients in a study from Spain), but the implications of this for surgical patient outcomes are unclear at the moment, except for postoperative adrenal insufficiencies (AIs). 90 On the other hand, patients with PA seem not to require routine evaluation for AI if concurrent hypercortisolism has been excluded preoperatively. 91 Several case reports and small cohort studies reported on the successful use of radiofrequency ablation (RFA) for the treatment of unilateral PA. 92 Current evidence comparing RFA with unilateral adrenalectomy for the treatment of PA is limited and variable.…”
Section: Public Health Perspective Of Primary Aldosteronismmentioning
confidence: 99%